Pneumatosis Cystoides Intestinalis in Patients with Systemic Sclerosis: A Case Report and Review of 39 Japanese Cases - Manabu Kaneko; Shin Sasaki; Shuzo Teruya; Kosuke Ozaki; Kazuhiro Ishimaru; Emi Terai; Hiroshi Nakayama; Toshiyuki Watanabe (Case Reports in Gastrointestinal Medicine)
Pneumatosis cystoides intestinalis (PCI) is a rare gastrointestinal complication of systemic sclerosis (SSc) characterized by intramural accumulation of gas within thin-walled cysts. We report the case of an 82-year-old female patient with pneumoperitoneum due to PCI associated with SSc and review the features of the 39 Japanese cases. The median patient age was 57 years (range 24–83 years) and the male/female ratio was 1 : 12. In the recent decade, 14 out of 15 cases (93.3%) evaluated with CT scans were diagnosed with PCI. The results suggest that CT scan may be a useful diagnostic tool for detecting PCI. PCI in patients with SSc is usually benign and requires only conservative therapy. However, two patients (5.1%) with signs of peritoneal irritation required surgery. When peritoneal irritation secondary to additional pathology is observed, surgical treatment may be warranted; a precise diagnosis for this condition is therefore essential.